Optical spectroscopic studied of emerging colloidal quantum dot : cesium lead halide perovskites (CsPbX3, X = Cl, Br, I) - Tan, Jia Hui (2016)
Colloidal quantum dots (CQDs) have been of great research interests for years, owing to the combination of quantum-size effects and enhanced optical properties, which positioned them at the forefront for future optoelectronic advancement. Additionally, CQD’s facile electronic and optical properties may be tuned to user’s preference by simply varying dot sizes and solution composition. Eventually allowing for convenient incorporation into various devices such as light-emitting diodes (LEDs), photovoltaic cells, telecommunication purposes, and bio-imaging for medical endeavor8. Though much effort and attention had been invested in hybrid organic-inorganic perovskites, research into pure inorganic perovskites has lagged behind greatly. One of which would be the all-inorganic cesium lead halide perovskites (CsPbX3, X = Cl, Br, I and its mixed halide systems). While the synthesis, crystallography and photoconductivity of direct bandgap CsPbX3 had been explored and reported approximately 50 years ago, it was never conducted in colloidal nanomaterial form9. Hence, this report focuses on 5nm – 10nm CsPbX3 nanocrystals (NCs) with cubic perovskites crystal structure, their optical properties, and its suggested applications. Optical measurements confirm that CsPbX3 NCs are not only photoluminescence (PL) active through the entire visible spectral region of 400nm – 700nm; they also display compositional tuning versatility, dot size-tunability, and both temperature and power – dependent PL. With the results, they realize new potential in the field of optoelectronic as CsPbX3 NCs provides a shift in status quo as compared to the commonly used colloidal CdSe/ZnS core/shell QD.